Autoantibodies against galectins are associated with antiphospholipid syndrome in patients with systemic lupus erythematosus - Sarter, Kerstin; Janko, Christina; André, Sabine; Muñoz, Luis E; Schorn, Christine; Winkler, Silke; Rech, Jürgen; Kaltner, Herbert; Lorenz, Hanns-Martin; Schiller, Martin; Andreoli, Laura; Manfredi, Angelo A; et al. (Glycobiology, 2013)
The presence of autoantibodies against immunoregulatory effectors can be relevant for onset and/or the progression of autoimmune disease. Emerging insights into an immunological activity profile including a role as opsonins give reason to systematically monitor sera of patients for immunoglobulin G (IgG) autoantibodies, preferably for several galectins at the same time. Here, we report on a study of chronic inflammatory rheumatic diseases, i.e. systemic lupus erythematosus (SLE; pilot cohort p, n = 40; confirmation cohort c, n = 109), rheumatoid arthritis (RA; p, n = 32; c, n = 25) and primary antiphospholipid syndrome (APS; c, n = 64). Enzyme-linked immunosorbent assay-based series using galectin-1, -2, -3, -4, -7, -8 and -9 and natural processing products, i.e. the truncated version of galectin-3 and the N-terminal domains of galectin-4, -8 and -9, were performed. Normal healthy donors (p, n = 20; c, n = 21) and patients with paraproteins (c, n = 19) served as controls. Highly significant optical density-value readings for IgG autoantibodies were consistently detected for the proto-type galectin-7 (SLE) and the tandem repeat-type galectin-8 and -9 (SLE and RA). Their presence was independent from the autoantibody status against double-stranded DNA (for patients with SLE) or a rheumatoid factor (for patients with RA), respectively. Importantly, anti-galectin-2 autoantibodies highly significantly correlated with the appearance of a secondary APS in patients with SLE so that this parameter may serve as an additional biomarker for APS. Equally of note, the presence of IgG autoantibodies against galectins capable to act as an opsonin may contribute to a sustained immune dysregulation in patients with chronic inflammatory rheumatic diseases.
Advance access publication on August 11, 2012
Gesehen am 31.01.2022